Global Cooperation Among G20 Countries Responding to the Crisis and Restoring Growth - Callaghan, Michael; Ghate, Chetan; Pickford, Stephen; Rathinam, Francis Xavier; SpringerLink (Online service) (New Delhi : Springer India : Imprint: Springer, 2014)
At the outbreak of the global financial crisis, 2008, the G20 was widely acknowledged as helping prevent an even more serious decline in the global economy. It helped to calm the panic in financial markets and articulate a set of possible policy options to restore global stability and growth. However, as the dual-track recovery set in, policy options for advanced economies and EMEs diverged. Within this context, this book will explore the scope for cooperation amongst the G20 and the diverging challenges and the intricate interconnectedness of policy options between advanced economies and the EMEs within the G20.
Chapter 1. Introduction -- Chapter 2. Keynote: The G-20 since 2008: Some reflections on the experience and the road ahead -- Part I: Eurozone Crisis: Short-Run Challenges and Options -- Chapter 3. Overcoming the Euro Area Crisis: Reforms and Results -- Chapter 4. Predicting the Euro: A Practitioner$1 (Bs Perspective -- Chapter 5. Monetary Integration in Europe and the Drawbacks of Centralization -- Chapter 6. Reflections on the Euro Crisis -- Part II: Rebalancing the Global Economy -- Chapter 7. The G20, IMF and Global Imbalances: The Policy Makers Perspective -- Chapter 8. Global Imbalances: Causes and Policies to Address Them -- Chapter 9. Exchange Rate Flexibility and Economic Rebalancing in China -- Chapter 10. Global Imbalances and Financial Fragility -- Part III: Financial Sector Regulation -- Chapter 11. Financial Regulatory Reforms: Not far enough or Overkill? -- Chapter 12. Asian Perspectives for Financial Regulatory Reforms after the Global Financial Crisis (GFC) -- Chapter 13. The Challenge of Financial Stability and Regulation from a European Perspective -- Chapter 14. Financial Regulatory Reforms: Striking a Balance -- Part IV: A New Framework for Reforming the International Monetary System -- Chapter 15. Reforming the International Monetary System: an Institutional Perspective -- Chapter 16. Strengthening the International Monetary System -- Chapter 17. System Sudden Stop(s), Credit Lines, and Funding Liquidity -- Part V: Capital Controls and Emerging Market Economies (EMEs) -- Chapter 18. Policy Tradeoffs in an Open Economy and the Role of G-20 in Global Macroeconomic Policy Coordination -- Chapter 19. Managing the Risks Associated with Volatile Capital Flows -- Chapter 20. On an Asian Monetary Union: What Does the Evidence tell Us? -- Part VI: Austerity and Growth -- Chapter 21. The Macro-economic Policy Response to the International Financial and Economic Crisis and the G20 -- Chapter 22. Austerity, Growth, and Public Policy -- Chapter 23. India and Fiscal Austerity.s
Keywords: Economics; Endogenous growth (Economics).; Economic policy; Macroeconomics; Finance; Economics/Management Science; Macroeconomics/Monetary Economics; Financial Economics; Emerging Markets/Globalization.; Economic Policy; Economic Growth